Hourglass of constant weight - Becker, Volker; Pöschel, Thorsten (Granular Matter, 2008)
In contrast to a still common belief, a steadily flowing hourglass changes its weight over the course of time (Shen and Scott in Am J Phys 53(8):787-788, 1985). We will show that, nevertheless, it is possible to construct hourglasses that do not change their weight. © 2007 Springer-Verlag.
Keywords: Granular flow; Hour glass flow